Desmoplastic fibroblastoma: A case series - Shuja Abbas, MBS, DPM; Breana Marine, DPM; Naomi Choi, MBA, DPM; Ian Richter, DPM, AACFAS; Arnold J. Zuckman, DPM, FABFAS (Foot & Ankle Surgery: Techniques, Reports & Cases)
Desmoplastic fibroblastoma is a rare, benign, slow-growing soft-tissue tumor that is typically found in subcutaneous or intramuscular tissue and can arise from various anatomical locations. The foot is a relatively uncommon site for this tumor. Due to its slow-growing nature and uncommon occurrence, it can be mistaken for other more common soft-tissue lesions. This article presents an atypical presentation of this neoplasm in the foot, aiming to raise awareness among pathologists and surgeons. Due to its rarity in podiatric practice, preconceived notions about its occurrence in this region are often absent. This case series emphasizes the need for comprehensive consideration in diagnosing and treating this neoplasm, thereby improving differential diagnoses, treatment plans, and patient outcomes.